The neurobiological basis of emotions and their connection to facial expressions in non-human mammals: insights in nonverbal communication - Mota-Rojas, Daniel; Whittaker, Alexandra L.; Bienboire-Frosini, Cécile; Buenhombre, Jhon; Mora-Medina, Patricia; Domínguez-Oliva, Adriana; Martínez-Burnes, Julio; Hernández-Avalos, Ismael; Olmos-Hernández, Adriana; Verduzco-Mendoza, Antonio; Casas-Alvarado, Alejandro; Lezama-García, Karina; et al. (Frontiers in Veterinary Science, 2025)
Recognizing that nonhuman animals are sentient beings has increased interest in studying their emotional state. Similar to humans, research has shown that some nonhuman mammals can modify facial expressions by contraction/relaxation of facial muscles according to their affective state. From a neurophysiological perspective, emotions are processed in several brain structures, mainly from the limbic system, such as the hypothalamus, hypophysis, hippocampus, prefrontal cortex, and amygdala. The converged pathways between the amygdala, the motor cortex, and its projections to the facial nerve control the movement of facial or mimetic muscles. Thus, facial expression is suggested to reflect the internal emotional state and could serve as an essential mode of nonverbal communication in mammals. In humans, the Facial Action Coding System (FACS) is a method that objectively analyzes facial movements using an anatomical base. In veterinary medicine, AnimalFACS is an adaptation of this system to eight animal species, including domestic animals (dogs, cats, and horses) and nonhuman primates (chimpanzees, orangutans, gibbons, macaques, and common marmosets). Considering these coded facial movements, current research aims to associate certain facial expressions with the animals’ emotional states and affective contexts. Thus, this review aims to discuss recent findings associated with the neurobiology of emotions and facial expressions in non-human mammals, using AnimalFACS to understand nonverbal communication. Characterizing each facial expression according to different contexts might help identify if the animal is expressing a positive or negative emotional response to the event, which can improve nonverbal human-animal communication.